ILRI 40 years hard talk: Livestock research general directions - International Livestock Research Institute (International Livestock Research Institute, 2014)
Brian Perry in conversation with Jimmy Smith, Carlos Sere and Hank FitzHugh. 'Hard talk' at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives, Addis Ababa, Ethiopia, 6–7 November 2014.